Assessment of earthquake-triggered landslide susceptibility considering coseismic ground deformation - Zhao, Yu; Huang, Zeng; Wei, Zhenlei; Zheng, Jun; Konagai, Kazuo (Frontiers in Earth Science, 2023)
The distance to the surface rupture zone has been commonly regarded as an important influencing factor in the evaluation of earthquake-triggered landslides susceptibility. However, the obvious surface rupture zones usually do not occur in some buried-fault earthquakes cases, which means lacking the information about the distance to the surface rupture. In this study, a new influencing factor named coseismic ground deformation was added to remedy this shortcoming. The Mid-Niigata prefecture earthquake was regarded as the study case. In order to select a more suitable model for generating the landslides susceptibility map, three commonly used models named Logistic Regression (LR), Artificial Neural Networks (ANN) and Support Vector Machines (SVM) were also conducted to assess the landslides susceptibility. The performances of these three models were evaluated with the receiver operating characteristic (ROC) curve. The calculated results showed the ANN model has the highest AUC (area under the curve) value of 0.82. As the earthquake triggered more landslides in the epicenter area, which makes it more prone to landslides in further earthquakes, the susceptibility analysis at two different mapping scales (the whole study area and the epicenter area) were also applied.